Increasing Students' Interest in Entrepreneurship Influenced by Entrepreneurial Attitudes and Motivation of Needs - Wahyuningsih, Dian; Pasaribu, Donald Frensius (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
Interest in entrepreneurship arises from a person's desire to start a new business. One of the driving factors for a person to become an entrepreneur is attitude. Entrepreneurship refers to the traits, character, and attributes possessed by individuals who have a strong drive to create innovative and creative ideas in every activity that produces results. This study aims to examine the effect of Entrepreneurial Attitudes and Needs Motivation on Student Entrepreneurial Interst in Langlangbuana University Students, Faculty of Economics and Business, Management Study Program, Class of 2020-2021. Using a method, the Proportionate Stratified Random Sampling technique with the Slovin formula of 75 students using descriptive and verification methods. Data analysis was carried out using Method of Succesive Interval (MSI) and Path Analysis assisted by the SPSS Program, as well as Hypothesis Testing. The results showed that the Entrepreneurial Attitude variable was good enough towards good, Motivation Needs were good enough towards good, and Entrepreneurial Interest was also considered goof enough towards good. Verification analysis shows that Entrepreneurial Attitude has an influence on Entrepreneurial Interest, Needs Motivation affects Student Entrepreneurial Interest of Langlangbuana University Students, Faculty of Economics and Business, Management Study Program, Class of 2020-2021.